Effects of statin therapy on outcomes of ischemic stroke: a real-world experience in Brazil - VITTURI, Bruno Kusznir; GAGLIARDI, Rubens José (Arquivos de Neuro-Psiquiatria, 2020)
Background: Statin therapy has become one of the most important advances in stroke secondary prevention. Objective: To provide evidence from real-world data for evaluating detailed associations between secondary prevention of stroke and statin use in Brazil. Methods: We conducted a prospective cohort study including consecutive patients diagnosed with an ischemic stroke. Subjects were classified into non-statin, simvastatin 20 mg, simvastatin 40 mg, and high-potency statin groups. We also registered the onset of statin therapy, previous use of statins, the adherence to medication, and if there was discontinuation of the therapy. After two years, the functional outcome, stroke recurrence, major cardiovascular events, and mortality were assessed. Results: Among the 513 patients included in our cohort, there were 96 (18.7%) patients without statins, 169 (32.9%) with simvastatin 20 mg, 202 (39.3%) with simvastatin 40 mg, and 46 (9.0%) with high-potency statins. Patients without statins were at increased risk of stroke recurrence and worse functional outcomes. Concerning etiology, evidence of beneficial use of statins was observed in cases of large-artery atherosclerosis, small-vessel occlusion, and stroke of undetermined cause. Those who presented poor adherence to statins or discontinuation of the treatment had worse prognosis after stroke whereas the early onset of statins use was associated with better outcomes. Patients with simvastatin 40 mg and high-potency statins presented the best functional recovery throughout the follow-up. Conclusions: Statins play an important role in the treatment of ischemic stroke, preventing stroke recurrence and cardiovascular events, and improving functional performance.
Keywords: Statin; Ischemic stroke; Outcomes; Prevention